Investigating cannabinoids and endocannabinoid receptors as drug targets for pain and inflammation - Marwarwa, Sinobomi Zamachi (Rhodes University, Faculty of Science, Department of Chemistry, 2020)
Cannabinoids and the endocannabinoid system have been studied in the past decades but have yet to be fully understood. An insight into interactions that occur between cannabinoid compounds and their receptors is important for understanding the cannabinoids and the endocannabinoid system. Cannabinoids are natural products found in some cannabis plants, and they have similar effects to endocannabinoids, which are chemicals in the body that are involved many aspects of health from appetite, memory, and movement to pain, inflammation and response to cancer. Cannabinoids have a high impact on the treatment of pain and inflammation, they show different antinociceptive mechanisms to existing drugs like opioids, also, they have antimigraine properties better than those achieved by aspirin. The CB1 and CB2 human receptors have been the most studied cannabinoid receptors. In this project, we used a combination of mass-spectrometry to generate plausible chemical fragments and computational techniques to assess the binding of these fragments to these two main CB receptors. CB1 was adapted from the protein data bank (PBD), file 5U09 and the CB2 model was predicted using the hierarchical protocol I-TASSER, starting from the amino acid sequence in UniProt (P34972 CNR2_HUMAN). The proposed active site for CB1 was reported in a publication accompanying the 5U09 PDB model, which was originally generated with a pre-existing ligand in the active site. However, CB2 had to be built from a homology model and the active site determined using a combination of I-TASSER, Maestro, and CASTp the more favourable binding energies were determined by CASTp, leading to the use of the CASTp coordinates as default for docking in the CB2 human receptor. The molecular docking of cannabinoids THC, CBD, CBDV, CBG and CBN on both the CB1 and CB2 proteins was performed to identify the amino acids that interact with these compounds at their active sites. This would provide a guide to a future fragment-based drug discovery (FBDD) synthesis project. The docking in this work showed adequate accuracy with binding energies between -8.23 kcal/mol and -9.97 kcal/mol for CB1 and between -6.78 kcal/mol and -7.74 kcal/mol for CB2. An observation made was that binding energies of the CB1 human receptor docking were higher than those of the CB2 human receptor, which could support the widely held belief that CB1 is more important in cannabinoid interactions. The cannabinoids were then subjected to collision-induced dissociation to produce fragment structures predicted in chapter 2. These hypothetical fragments were docked in the CB1 and CB2 human receptor, the general trend again being the binding energies for the CB1 receptor was again around 10% higher than those of the CB2 receptor. As expected, larger fragments tended to have better binding, with the fragment proposed from m/z 259 with binding energies -9.62 kcal/mol in CB1 and -6.26 kcal/mol. Those fragments with significant lipophilic side chains or some aromatic moiety also showed good binding or around -6.00 kcal/mol, similar to the intact cannabinoids. In our case, this fragment was proposed from m/z 223 with binding energies -7.71 kcal/mol in CB1 and -6.5 kcal/mol in CB2. The results from the fragment dockings were favourable in that they have binding affinities lower than -6.0 kcal/mol which is good enough for the structures to be leads in the creation of fragment libraries. The docking was performed with Autodock 1.5.6 and data visualization with a discovery studio.
Keywords: Cannabinoids; Cannabinoids Receptors; Inflammation -- Alternative treatment; Pain -- Alternative treatment; Drug targeting